A review of the millipede genus Dorypetalum Verhoeff, 1900 (Diplopoda: Callipodida: Dorypetalidae) - Stoev, Pavel; Enghoff, Henrik (Zootaxa, 2006)
A new millipede species, Dorypetalum helenae (Callipodida: Dorypetalidae), is described from the Kuru Dağ Mts, European Turkey. The species is morphologically close to D. bulgaricum from the Rhodope Mts, SE Bulgaria but is well distinguished by the particular, racket-shaped mesal coxosternal process of gonopods. All hitherto described species in the genus are reviewed, and new illustrations are provided for D. bosniense and D. trispiculigerum. A new key for identification of the species in the genus is made to accommodate the new findings.